## Simplify: (4x^3 y^2)(2x^2 y^3)

<p>To simplify this expression, we can use the product rule of exponents, </p><p>which tells us that a^m * a^n = a^(m+n). Applying that rule, we get:</p><p>(4x^3 y^2)(2x^2 y^3) = 8x^(3+2) y^(2+3) = 8x^5 y^5</p>

<p>To simplify the expression (4x^3 y^2)(2x^2 y^3), we can use the laws of exponents and the distributive property of multiplication:</p><p>(4x^3 y^2)(2x^2 y^3) = 4 * 2 * x^3 * x^2 * y^2 * y^3 = 8x^(3+2) * y^(2+3)</p><p>Simplifying the exponents, we get:</p><p>8x^5 y^5</p><p>Therefore, (4x^3 y^2)(2x^2 y^3) is equal to 8x^5 y^5.</p><p><br></p>

Post your answer

Sign in to post your amazing answer.